2023
DOI: 10.1007/s11102-023-01309-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in refractory hormone-producing pituitary adenomas: an unmet need

Abstract: Purpose To describe quality and outcomes of patient-reported outcome (PRO) measures (PROMs) used in patients with refractory hormone-producing pituitary adenomas, and to provide an overview of PROs in these challenging pituitary adenomas. Methods Three databases were searched for studies reporting on refractory pituitary adenomas. For the purpose of this review, refractory adenomas were defined as tumors resistant to primary therapy. General risk of bias w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…While various questionnaires and scales can be useful to measure quality of life in patients, they are still fraught with inconsistent application and risk of bias. A recent review by van Trigt et al analyzed 20 studies reporting patient-reported outcome measures in patients with refractory hormone-producing adenomas, and found significant variance in conclusions across the studies, compared to patients in biochemical remission [51]. Digital phenotyping has become increasingly utilized, in which data from personal digital devices, in particular smartphones, are gathered to measure behavioral patterns pertaining to sleep, physical mobility, social interactions, and cognitive functioning, among others [52].…”
Section: Plos Onementioning
confidence: 99%
“…While various questionnaires and scales can be useful to measure quality of life in patients, they are still fraught with inconsistent application and risk of bias. A recent review by van Trigt et al analyzed 20 studies reporting patient-reported outcome measures in patients with refractory hormone-producing adenomas, and found significant variance in conclusions across the studies, compared to patients in biochemical remission [51]. Digital phenotyping has become increasingly utilized, in which data from personal digital devices, in particular smartphones, are gathered to measure behavioral patterns pertaining to sleep, physical mobility, social interactions, and cognitive functioning, among others [52].…”
Section: Plos Onementioning
confidence: 99%